Localization of endogenous activity of phospholipases A and C in Ureaplasma urealyticum. - De Silva, N S (1991)
Endogenous activities of phospholipases A and C in Ureaplasma urealyticum were assayed in cellular fractions of exponential-phase cells. Enzymatic studies indicated that ATPase activity was localized in the plasma membrane fraction and NADH and NADPH dehydrogenase activities were localized in the cytosol fraction. Studies with purified ureaplasma membranes demonstrated that, of three serovars tested, endogenous phospholipase A1, A2, and C activities were localized in the plasma membrane. Very low levels of activity were observed in the cytosol fractions. Phospholipase A2 activity in the plasma membrane was 3- to 5-fold higher than the activity in the lysates and 60- to 300-fold higher than the activity of phospholipase A1. Phospholipase C was localized mainly in the plasma membrane, with 20% found in the cytosol fraction. The levels of activity were comparable among the three serovars. There was a significantly lower level of activity in cells from the stationary growth phase than in the exponential phase. Significant differences were observed in the phospholipase A activities among the U. urealyticum serovars 3, 4, and 8. Phospholipase A2 activity was twofold higher in serovar 8 membranes, and phospholipase A1 activity was twofold higher in serovar 3 membranes. These results demonstrate that endogenous activities of phospholipase A and C are localized primarily in the plasma membrane fraction of U. urealyticum. The specific activities in the membranes of the phospholipases varied among the three serovars. Phospholipase enzymes may function as virulence factors in U. urealyticum and may vary among the serovars.